PERAN ELECTRONIC DATA PROCESSING TERHADAP PENGENDALIAN AKUNTANSI - ALVIN RICARDO (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
The application of technology in enterprise information systems should consider the users of the system so the technology can be useful applied in accordance with the duties and ability of the user. The purpose of this paper is to determine whether a computer program has to process a transaction with the balance of the auditor testing benar.Dalam computer will check whether the contents of the master file and transaction file is the result of a computer process. Furthermore, the computer will greatly assist independent auditors in performing analytical procedures. Computers can quickly perform ratio calculations, trend analysis, calculate percentages and others. Auditing concepts relating to risk assessment and how to test and other tests performed to obtain sufficient evidence to support the independent auditor's opinion. In assessing control risk for a company that uses computer technology, an independent auditor should consider control risks arising as a result of use of computer technology.